(untitled) (Journal of the College of Education for Women, 2019)
Many Iraqi students are reluctant to actively participate in the Englishlanguage classroom. This reluctance is attributed to a number of factors, above whichis students’ lack of thinking skills necessary to express their points of view. Thiseventually results in passive learning, a real problem in English language learning inIraq.A need for educational reforms and innovations seems essential. These involvedeveloping relevant teaching materials, adopting learner-centered approach,promoting learner autonomy, and enhancing critical thinking.This study is hoped to assist teachers of English to initiate change and fosterthe expansion of thinking, and adopt various new strategies to increase classroomparticipation. The paper also aims to enable Iraqi students to be active thinkers ratherthan passive attendees.